(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Stress and anxiety adversely affecting on human being especially among children when they are separated from parents and gothospitalized. This planned study evaluating effectiveness of pre-visualization of nursing procedures to minimize stress and anxietyamong hospitalised children.Aim: To minimize stress and anxiety of hospitalised children related to nursing proceduresSettings and Design: This study is planned at tertiary care hospitals from Karad tehsil Maharashtra, by using Quasi experimental nonrandomized control group design.Methods and Material:400 (200 control & 200 experimental) Hospitalised children between the age group of 6 years to 10 years, whoare undergoing selected nursing procedures and willing to participate will be included in the study by using non-probability convenientsampling technique. For assessing anxiety and stress, Venham Picture Test (VPT) and Children’s Emotional Manifestation Scale(CEMS) will be used respectivelyStatistical analysis used: Data will be analysed in terms of objectives by using Descriptive and Inferential statistics.To find the association chi square test and to find co-relation between variables Pearson’s co-relation coefficient test will be used.Conclusion: pre-visualization may help children to reduce their nursing procedure related stress and anxiety and cooperate to nurses forthe same.